FUNGSI TAMAN KOTA DHARMA WANITA BAGI MASYARAKAT KOTA PEKANBARU - Mubarok, Muhammad Zaki; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Humans need enough space for day-to- day activities, with so many buildings madespecifically for each different activities, one of which is a Dharma Wanita City Park. Thispark is created to provide an open green space for the city of Pekanbaru, this green space willbe expected to give a sense of calm, relief and socialization media that seem natural for thesociety. In the middle of human dense activity present with a variety of jobs and the numberof events in the society, city parks is expected to also provide a place for other publicactivities that will make this park is always crowded and increasingly famous in the midst ofsociety, so that the function of the garden this can be updated and running properly. Thepurpose of this study was to determine the function of Dharma Wanita city park for thesociety of Pekanbaru city, the less visible any facility that serves the park so as to makevisitors comfortable and want to come back to visit, over time this will help managers andgovernment to renew the facility in case had to be replaced and that should be added. Thetheory that used in this study are functional theory. While the quantitative method used isdescriptive, using accidental sampling technique with the questionnaire data collection andobservation. The number of respondents in this study were as many as 25 people. Based onthe research results of almost all of the respondents were happy in this city park, in additionto making the city more fresh and beautiful, also provide a natural alternative mediasocialization for the Pekanbaru city, visitors coming from the children, adolescents andadults. Average visitor age is 21-30 years old. information about the city park function anddata is obtained from respondents who visited the park and from the agencies that responsibleof this city park.Keywords : Functionalism, Garden City, Society